Pentingnya Bank Syariah Dalam Mengelola Keuangan Masyarakat Indonesia - Laelatur Rohmah; Desy Meina Indrasari; Agus Eko Sujianto (Jurnal Akuntan Publik, 2023)
Indonesia, which is a country with a very large population, has a fairly stable economy. This study aims to determine the importance of Islamic banks in managing the finances of indonesia society. The method used in this research is literature study, in which literature study is a data collection method that is carried out by taking research information that is in accordance with the research theme. This information can be obtained from various reference sources, both in the form of written documents, in the form journals and articles, pictures, or electronic documents that can support the process of writing research papers. From this study, the results show that Islamic banks are banks that have good potential for the economy in Indonesia. With Islamic banks, muslim people no longer need to be afraid of transactions what he did. However, basically Islamic banks in Indonesia are still lagging behind conventional banks because the development process of conventional banks is much faster than Islamic banks.